Экономическая культура как социологическое понятие - Ефременко, Т. (Социология: теория, методы, маркетинг, 2005)
The article is dedicated to the whole theoretical conception of economic culture as important category of economic sociology. The main theoreticalmethodological principles needed for research of this complicated and manysided concept are formulated. Economic culture is considered as the totality of economic knowledge, abilities of their application and values regulating human economic behavior. The main approaches to an empirical evaluation of this social phenomenon are also presented in the article.